Peran Psikologi Arsitektur dalam Mewujudkan Ruang Publik Terpadu Ramah Anak di Dataran Engku Putri Batam - Carissa Dinar Aguspriyanti; Benny Benny; Rika Ayunda; Nadiah K. Artanti; M. Zidane Khairi; Fedrico Tysen; Stivani Ayuning Suwarlan (Universitas Sebelas Maret Surakarta, 2024)
Considering the needs of children as users is essential when creating Child-Friendly Integrated Public Spaces (RPTRA). Hence, this study sought to explore how the psychology of architecture focused on user psychology and behavior can contribute to the creation of RPTRAs. This research at Dataran Engku Putri, Batam City, utilised qualitative descriptive methods involving literature study and observation techniques. The results revealed that this public space was less adequate in meeting the RPTRA criteria including security and safety, recreational function and comfort, ease of accessibility, park attractiveness, health, meeting social needs, and learning elements. Therefore, it is necessary to improve and develop specialised play facilities for children based on the five aspects of psychology of architecture, namely space, size and shape, furniture and its arrangement, colour and texture, sound, temperature, and lighting.